A Escrita virtual na adolescência: os blogs como um tratamento do real da puberdade, analisados a partir da função do romance - Nadia Laguardia de Lima (2009)
The purpose of this work is to investigate the role of blog writing by adolescents in contemporary times, supported by theoretical psycho-analytical resources. In making such a reflection, our study has taken two guiding lines: the first relates writing to culture and the second analyzes the role of writing in puberty time. We sustain the hypothesis that intimate diaries have the novel as their paradigm. Puberty is a period in which one meets the reality of sex, promoting the unfastening of the knot that ties the three stages of psychic reality. The writing of a familiar novel can operate in the construction of the adolescent symptom. Our research identifies three kinds of blogs produced by teenagers, from a novel perspective: as a writing to achieve pleasure; as a writing practice by oneself; and the third type of blog writing which corresponds to a novel, as a product of acknowledgment to the other, allowing social bonds. The first two types do not establish a social link, which can be considered an outcome generated by the capitalist discourse, whereas the last type presents the production of a character as the main protagonist of his/her own story, promoting a change of the subject position so that one, rather than being determined by history, is able to read ones historical determination.